Evolving the method: Grounded theory in the context of post-hoc analysis - Sean Courtney; Wayne Babchuck; Jha LaDeane (Adult Education Research Conference, 1994)
In a study of student experiences in an ABE/GED program, three researchers collaboratively engaged in a process of learning grounded theory (GT) while simultaneously conducting research on a population of adult learners. This paper reports the conduct of the study, paying particular attention to how participants were sampled, how the coding evolved, and how the eventual theory emerged. The paper concluded with some reflections on the practice of grounded theory research.